2002
DOI: 10.1037/0278-6133.21.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Personality, personal model beliefs, and self-care in adolescents and young adults with Type 1 diabetes.

Abstract: This study compared 3 models of association between personality, personal model beliefs, and self-care in a cross-sectional design. These models were as follows: (a) Emotional stability determines self-care indirectly through personal model beliefs, and conscientiousness is a direct predictor of self-care; (b) emotional stability determines selfcare indirectly through personal model beliefs, and conscientiousness moderates the association between beliefs and self-care; (c) both emotional stability and conscien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(96 citation statements)
references
References 54 publications
6
89
0
1
Order By: Relevance
“…They focused on adult diabetic patients because of the extensive self-management necessary to manage this disease, including daily injections of insulin, regulation of food intake, the monitoring of glucose levels (often including journal entries), and daily life-style choices. Indeed, abundant research shows that the successful management of diabetes requires high levels of C (Lawson, Bundy, Belcher, & Harvey, 2010;Skinner, Hampson, & Fife-Schaw, 2002;Vollrath et al, 2007). Yet, their study points to diverse mechanisms by which C behaviors likely yield more efficacious management of diabetes in the upper/middle-class clinic ("Park Clinic") than in the workingclass/uninsured clinic ("County Clinic"), illustrating how social circumstances apparently moderate the impact of C behaviors, and also the value of such ethnographic studies.…”
Section: The Disabling and Double Disablement Hypothesesmentioning
confidence: 99%
“…They focused on adult diabetic patients because of the extensive self-management necessary to manage this disease, including daily injections of insulin, regulation of food intake, the monitoring of glucose levels (often including journal entries), and daily life-style choices. Indeed, abundant research shows that the successful management of diabetes requires high levels of C (Lawson, Bundy, Belcher, & Harvey, 2010;Skinner, Hampson, & Fife-Schaw, 2002;Vollrath et al, 2007). Yet, their study points to diverse mechanisms by which C behaviors likely yield more efficacious management of diabetes in the upper/middle-class clinic ("Park Clinic") than in the workingclass/uninsured clinic ("County Clinic"), illustrating how social circumstances apparently moderate the impact of C behaviors, and also the value of such ethnographic studies.…”
Section: The Disabling and Double Disablement Hypothesesmentioning
confidence: 99%
“…It can lead to violation of social norms (Cooper, Wood, Orcutt, & Albino, 2003;Lynam, 1996) and thereby to interpersonal conflict. The potential adverse results range widely, including disruption of marital stability (Kelly & Conley, 1987), job performance (Hogan & Holland, 2003), and health-maintaining behaviors (Bogg & Roberts, 2004;Hampson, Andrews, Barckley, Lichtenstein, & Lee, 2000;Hampson, Severson, Burns, Slovic, & Fisher, 2001; T. C. Skinner, Hampson, & Fife-Schaw, 2002). Thus, consistent expression of impulses without regard to the future and without regard to the needs of others can adversely affect both individual well-being and social relations (Tangney, Baumeister, & Boone, 2004).…”
mentioning
confidence: 99%
“…Both coping and illness perceptions have been found to mediate the relationship between personality and health 17 outcomes in adolescents with other chronic diseases such as Type 1 diabetes and asthma [12,48,49]. Although a recent study demonstrated the predictive value of patients' illness perceptions for their quality of life two years later [50], very few studies to date have focused on the illness perceptions and coping strategies of individuals with CHD.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 99%